Streaming Colors of The Youth: A Textual Analysis of LGBTQ+ Animated Netflix Original Cartoon Series of the Generation Alpha - Aguila, Candice Margareth G. (Animo Repository, 2024)
With the evolving technological advancements, media can now be consumed on multiple platforms. Netflix is the top platform with the highest number of users, with around 38.1% dedicated to streaming. In addition, LGBTQ+ media consumption has contributed to the increasing number of people identifying as LGBTQ+ in recent times. Ensuring that the next generation of young, impressionable youths would have a better identity formation and social acceptance, it is suggested to create more child-oriented cartoons filled with positive LGBTQ+ representation to pave a path for more inclusive and diverse outlooks – mending the gap of the current disconnection between the perceptions of what LGBTQ+ representation means to society. Therefore, this study applied a textual analysis by comparing and analyzing three modern Netflix LGBTQ+ cartoons to real-life experiences of LGBTQ+ youths to determine the current status of its representation in media. From the results, we have concluded that there was a significant improvement in LGBTQ+ representation in Netflix cartoons as the series progressively became bolder in tackling topics of gender and sexuality by incorporating these themes in their stories. With the study being limited to three Netflix series, it is recommended that future researchers continue this kind of research on a larger scale — considering whether the findings of this study and previous studies would still align in the future.